Adaptive control scheme based on transient stability mechanism for photovoltaic plants. Issue 22 (5th October 2020) - Yu, Moduo; Huang, Wentao; Tai, Nengling; Xi, Xinze; Nadeem, Muhammad Haroon
Abstract : The world‐wide application of photovoltaic (PV) plants is a promising solution to the energy crisis. However, PV plants usually suffer from transient instability due to weakness in dynamical adaptability. This study, based on the transient stability mechanism, devises an adaptive control scheme to achieve transient stability enhancement for PV plants. The transient stability mechanism shows that the active droop factor is negatively associated with the transient stability whereas the reactive droop factor is positively associated. The transient stability enhancement is implemented by increasing the reactive droop factor and reducing the active droop factor to raise the power angle curve. The proposed control scheme adjusts the droop factors dynamically during the transient events by detecting the real‐time electrical quantities. The control scheme advances in a designed activation module which is able to judge if there exist transient events. A series of simulation cases demonstrate the effectiveness of the control scheme in different transient events. Simulation results show that the control scheme adjusts droop factors adaptively and possesses better transient stability than the normal droop control.